THE ROLE OF VIRTUAL FIGURES IN FORMING STUDENTS MORALS: AN EXPLORATIVE STUDY AT MTsN 2 MOJOKERTO - Maghfirotillah, Ana Rohilah Ila; Yaqin, Ainul; Alivi, Justsinta Sindi (PROGRES PENDIDIKAN, 2025)
This study explores examples of moral role models experienced by students at MTsN 2 Mojokerto in the current digital era. The moral role models in question refer to the influence of public figures' behavior on social media on students' character. The method used was a qualitative approach with phenomenology. The research subjects consisted of 15 students and two Akidah Akhlak teachers, selected through purposive sampling. Students were chosen as informants because they frequently use social media, which allows them to follow public figures and are able to convey their views and experiences well verbally. Akidah Akhlak teachers were chosen because they play a direct role in shaping character and instilling moral values in the madrasah environment. The results of the study show that moral development occurs through three stages: accessing digital content, absorbing moral messages, and imitating attitudes. Students view virtual figures as modern role models, while teachers function as guides through positive content recommendations, class discussions, and limiting cell phone use. Social media has varying impacts on students' morals, depending on how well they imitate and understand. The novelty of this research lies in its focus on the phenomenon of virtual role models in madrasah environments, as well as its analysis of the relationship between the influence of digital role models and the educational methods teachers employ in shaping Islamic morals in the age of social media. This research contributes to designing moral education strategies in the digital era that are relevant and appropriate to the challenges students face.